Decomplexation of Venom Proteome of Pakistani Cobra (Naja naja naja) : Decomplexation of Venom Proteome of Pakistani Cobra (Naja naja) - Sadia Erum Khan; Humera Waheed; Syed Faraz Moin (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
The venom proteome of Naja naja from Sindh, Pakistan was decomplexed utilizing reverse phase HPLC and SDS PAGE. The results were compared with already reported Naja naja species of the region. The banding pattern represents all the major families of proteins including three-finger toxins, phospholipase A2, snake venom metalloproteases, L-amino acid oxidases, phosphodiesterase, nucleotidases, cysteine-rich secretory proteins, serine proteases, nerve growth factor, cobra venom factor, acetylcholinesterases, Kunitz-type serine protease inhibitors and C-type lectin proteins. The decomplexation of the venom showed the best possible separation through RP-HPLC elution of venom components containing small peptides, small and large proteins based on hydrophobicity. The SDS PAGE under reducing and non-reducing conditions of HPLC fractions highlighted the presence of several proteins.